Phase modulator based on Silicon-on-Insulator (SOI) rib waveguide - Mardiana, Bidin; Haroon, Hazura; Hanim, Abdul Razak; Sahbudin, Saari; Abdullah, H. (2010)
This paper presents the study of electrical characteristic of phase modulator in the carrier injection mode. The phase modulator device has been integrated in the silicon-oninsulator (SOI) rib waveguide by using the p-i-n diode structure. The electrical device performance is predicted by using the 2-D semiconductor package SILVACO (CAD) software under DC operation. In summary, the phase modulator device required 0.035mA drive current to get phase shift at wavelength 1.55μm meanwhile 0.066mA drive current is required for the 1.3μm wavelength.